Framing #Ferguson: A comparative analysis of media tweets in the U.S., U.K., Spain, and France. (October 2019) - Harlow, Summer
Following the killing of unarmed teenager Michael Brown in Ferguson, Missouri, protests around the world—online and offline—grabbed headlines. Considering that previous research suggests that the news media tend to follow a protest paradigm of coverage that delegitimizes protesters, this study examined #Ferguson coverage on social media to re-assess the relevance of the paradigm. Using computer analysis, this study analyzed thousands of tweets posted by news organizations and individual journalists in the U.S., U.K., Spain, and France, as well as the general public's tweets, to compare how race, police brutality, and the protests were discussed across countries. Findings fill the gap in the literature as to whether delegitimizing, paradigmatic coverage extends to Twitter, pointing to differences not just between countries, but also between media outlets and individual journalists, and between the public and the journalism industry. Implications for future research are discussed.